Virtual hearings in labor lawsuits and their validity after the COVID-19 pandemic - Salinas Avila, Javier Naval (2022)
The implementation of virtual hearings in Peru is the product of a rule dictated by the Judiciary due to the national state of emergency caused by the COVID-19 pandemic. It is a well-known fact that the purpose of this ruling was to reestablish the administration of justice in the country; however, being on the verge of overcoming the health crisis, it is vital to analyze and evaluate its validity with the aim of offering the procedural party a modern labor lawsuit, based on technological and electronic tools, within the context of the strengthening and consolidation of the use of information and communication technologies in the Peruvian legal labor system.